A review of the nutritional value and biological activities of sturgeon processed byproducts - Chen, Rui; Liu, Zhe; Wang, Jinze; Jin, Wengang; Abdu, Hassan Idris; Pei, Jinjin; Wang, Qi; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
Sturgeons are widely distributed, rich in nutrients, have few diseases during the breeding process, are easy to breed and are rich in production capacity. However, at present, the sturgeon industry has the problems of a single product structure and a short industrial chain. The main products are mainly sturgeon meat. Due to its high fat content and difficulty in removing the fishy smell, the market sales situation is poor. In this context, it is very important for the development of the sturgeon industry to carry out research on the nutritional value of sturgeon processing byproducts and develop diversified products. Therefore, this paper summarizes the research on the nutritional value of sturgeon processing byproducts and the current situation of processing and utilization over the past 10 years. First, CiteSpace visual analysis software and the bibliometric analysis platform were used to analyze the status of sturgeon research, and the Web of Science database was used as the literature source to fit the keywords of sturgeon literature in the past ten years. After excluding the two keywords sturgeon and sturgeon meat, the relevant literature is analyzed and sorted, focusing on the literature in the last five years. Second, a comprehensive and in-depth review (sturgeon, processing, byproducts as the keywords to search Google Scholar and Web of Science) was conducted on the research of the nutritional components contained in sturgeon and the processing of nutritional components in byproducts to provide an effective reference for the research and processing of the sturgeon industry.